Classroom Strategies through Translanguaging for Multilingualism Students - Rachmi Retno Nursanti (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2021)
This research aims to discover translanguaging strategy in the process of teaching English material to multilingualism students. Due to the Indonesian country is a multicultural, the children got their mother tongue is a local language, not Bahasa Indonesia as the national ones. The Indonesian students acquire two languages n their daily life; local language and Bahasa Indonesia. Therefore, the role of English teacher is to explain English materials using English as the target language, local language and Bahasa Indonesia to increase students’ comprehension. This research used qualitative research with grounded theory design. In collecting the data, the researcher used interview technique to discover further information. In this research, the use of L1 was mostly used in the classroom rather than L2. The students could understand the material because the teachers’ effort to translate the language from Bahasa Indonesia to English and vice versa. This phenomenon was challenging because of the lack of students’ confidence to practice English. However, translanguaging decreased students’ anxiety in the class because they could understand English well by using two languages; Bahasa Indonesia and English. the findings are easy to be implemented by the following teachers in teaching multilingualism students for non-English speaking country, because translanguaging facilitates students and teachers to learn English using affordable way.